(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The goal of this study was to look at quinolone-resistant (QR) Escherichia coli (E. coli) from retail beef and poultry meat in Egypt by looking at the QR mechanisms in the resistant strains. Materials and Methods: In total, 120 samples of raw poultry meat (n = 60) and beef meat (n = 60) were purchased from Mansoura retail stores between January and March 2021, and evaluated microbiologically for E. coli. Then, an antimicrobial sensitivity test was applied to all isolates. The prevalence of QR E. coli with concern for the QR determinants, including quinolone resistance-determining regions (QRDRs) mutations, the plasmid-mediated quinolone resistance gene (PMQR), and the efflux pump activity were determined. Results: The total prevalence of E. coli was 34.2% (41/120). Noticeably, the prevalence of E. coli in poultry meat (40%, 24/60) was higher than that of beef (28%, 17/60). All strains were assessed for their antimicrobial susceptibility using the disc diffusion technique; the highest rate of resistance (100%) was displayed to clindamycin and cefuroxime, followed by ampicillin (97.6%), doxycycline (92.7%), amoxicillin-clavulanate (92.7%), nalidixic acid (NA) (80.5%), sulfamethoxazole/trimethoprim (70.7%), chloramphenicol (63.4%), gentamicin, and azithromycin (58.5% each). Multiple antimicrobial resistance (strains resistant to three or more antimicrobial classes) was displayed by 97.6% of E. coli isolates. Regarding QR, 37 isolates could resist at least one of the examined quinolones. Regarding PMQR genes, qnrS was determined in 70% (7/10) of QR E. coli, while qnrA, qnrB, and qnrD were not identified. While the mutations determined regions of QR in the resistant E. coli isolates, S83L was the most prevalent in gyrase subunit A either alone or combined with D87N and D87Y, and three isolates of QR E. coli isolates revealed a topoisomerase IV subunit mutation harboring S80I. 20% of the isolates displayed efflux activity, as NA showed a considerable difference between its zones of inhibition. Conclusion: The high prevalence of antimicrobial-resistant E. coli, with concern for QR strains harboring different resistance mechanisms in poultry meat and beef, threatens the public’s health. Thus, standard manufacturing procedures and adequate hygiene conditions must be followed in all phases of meat preparation, production, and consumption, and public knowledge should be improved. J. Adv. Vet. Anim. Res., 10(3): 490–499, September 2023 http://doi.org/10.5455/javar.2023.j702